Measurement of the probability of gluon splitting into charmed quarks in hadronic Z decays - Dova, María Teresa (2000)
We have measured the probability, nga cc , of a gluon splitting into a charm-quark pair using 1.7 million hadronic Z decays collected by the L3 detector. Two independent methods have been applied to events with a three-jet topology. One method relies on tagging charmed hadrons by identifying a lepton in the lowest energy jet. The other method uses a neural network based on global event shape parameters. Combining both methods, we measure <mtext>n</mtext><mtext>g→c</mtext><mtext>c</mtext><mtext>̄</mtext><mtext>=[2.45±0.29±0.53]%</mtext>.